Preliminary Study of pH, EC, TDS, and Heavy Metals Analysis of Oxbow’s Sediments in Bandung Region - Alfitrah, Siti Percika; Kirana, Kartika Hajar; Fitriansyah, Rd Agung; Shafaria, Mileani (Universitas Islam Negeri Ar-Raniry, 2024)
The Oxbow Lake is a vital part of river and it usually used for household, agricultural, and fisheries needs. The oxbow lake faces pollution risks from human activities. This study aims to assess the quality of water and sediment by pH, EC, and TDS of water and sediment as well as heavy metal content in sediment. The results show that the environmental conditions of the oxbow lakes around the Upper Citarum River are generally good because they fall within the safe limits for hygiene and sanitation standards, except for Babakan Patrol Oxbow Lake and Sapan Oxbow Lake. Unfortunately, the heavy metal levels in samples O1-2, O4-2, and O7-1 exceed sediment quality guidelines. These measurements indicate evidence of anthropogenic influence on sediment samples.